The Effect of Managerial Ownership on indebtedness Percentages in Light Finical Characteristics and Ownership Structure Companies Case Study in Jordanian - مؤيد محمد علي الفضل; أزهر صبحي الجبوري (Iraqi Journal for Administrative Sciences, 2024)
The study aimed to examine the relationship between managerial ownership and the debt ratio in order to determine whether managerial ownership has an important impact in determining the composition of the capital structure or not, in light of a set of financial characteristics of the company, at times, and at other times in light of the components of the ownership structure, as variables controlling the behavior of the company. Managers trend of gearing ratio. The study was conducted on a sample of 87 companies registered on the Amman Stock Exchange for the period 2010 - 2014. The results of testing the first hypothesis supported the effect of the incentive to rely on debt when the percentage of managerial ownership is low and supported the effect of protection when the percentage of managerial ownership is high. The results of testing the second hypothesis also supported the intellectual orientations of previous studies regarding the inverse relationship between the concentration of administrative ownership and the debt ratio, and that the role of ownership structure in influencing this relationship depends on the hypothesis of convergence of interests.